Method Of Treatment Of Cholelithiasis In Children (Eurasian Medical Research Periodical, 2023)
The problem of cholelithiasis in pediatrics is extremely relevant today, which is explained by the annual increase in the number of detected cases and difficult diagnosis. Blurred and unexpressed clinical symptoms do not allow suspecting the formation of stones in the gallbladder in the early stages. Many questions remain regarding the choice of tactics in relation to treatment options for gallstone disease in childhood. For a long time, gallstone disease has traditionally been considered a pathology of adults. Accordingly, almost the entire volume of scientific research was devoted to the diagnosis and treatment of this pathology in the above group of patients